Antibiotic Resistance Patterns of Listeria Species Isolated from Broiler Abattoirs in Lusaka, Zambia - Prudence Mpundu; John Bwalya Muma; Andrew Nalishuwa Mukubesa; Henson Kainga; Steward Mudenda; Flavien Nsoni Bumbangi; Walter Muleya; Patrick Katemangwe; Musso Munyeme (Antibiotics, 2022)
L. monocytogenes is a public health threat linked to fast foods such as broiler chickens. This study aimed to verify the occurrence of Listeria species in chickens from abattoirs and evaluate their antimicrobial resistance. In total, 150 broiler carcass swabs distributed as cloacal (n = 60), exterior surface (n = 60), and environmental (n = 30) were collected. Listeria species were characterized using biochemical tests and PCR. We conducted antibiotic resistance tests using the disc diffusion and Etest (Biomerieux, Durham, NC, USA) methods. Overall isolation of Listeria species was 15% (23/150) 95% CI (10.16–22.33), 2% (3/150) 95% CI (0.52–6.19) and 13% (20/150) 95% CI (8.53–20.08) came from environmental swabs and carcass swabs, respectively. Proportions of positive Listeria isolates were L. monocytogenes 74% (17/23), L. welshimeri 22% (5/23), and L. innocua 4% (1/23). Listeria species from the exterior carcass swabs was 61% (14/23), cloacal swabs 26% (6/23), and environmental swabs 3% (3/23). L. monocytogenes had the greatest resistance percentage to the following antibiotics: clindamycin (61%, 10/23), tetracycline 30% (7/23), and erythromycin 13%, (3/23). Isolation of L. monocytogenes in relatively high numbers, including the antimicrobial profiles, suggests a potential risk of the pathogen remaining viable in the food continuum and a public health risk to would-be consumers.